(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we address a new product in the category of tangle-oids which we call additive product. We prove that this additive product with formal addition on tangle-oids gives us associative algebra. Last we give the relationship between this new product, and tensor and compositions on tangle-oids.